Luciano Floridi’s project of the philosophy of information - Dabrarodni, Danila G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Luciano Floridi is one of the leading experts in the field of modern philosophy of technology and the author of the original tetralogical project of philosophy of information. Philosophy of information is defined as a philosophical field concerned with the critical investigation of the nature and basic principles of information, as well as the application of information-computational methodologies to philosophical problems. The concept of information is the central category of ontology, all objects are represented as informational, and the system of them on the scale of the Universum is the infosphere. All information objects (animate or inanimate) are equivalent, this is the basis of the ethics of information. Evil is everything that causes the destruction of the infosphere, good is everything, which contributes to the growth of the infosphere.